Kepribadian Introvert Tokoh Utama dalam Novel Aku Mencintaimu Seluas Ikhlasku Melepaskanmu Karya Sarah Aulia - Bahriyanti, Anis; Sari, Ni Wayan Ayu Permata; Sudrajat, Yayan (PT. LANCAR MEDIA KOMUNIKASI, 2024)
The aim of this research is to analyze the introverted personality of the main character in the novel Aku Mencintaimu As Widly as My Sincerity Lets You Go by Sarah Aulia to reveal the introverted personality of the main character. Apart from that, the researcher hopes that readers will understand the novel better. The research method used to analyze this novel is the library method, which means the author looks for material or data sources through relevant books as a theoretical basis. The focus is on the introverted personality which is divided into four functions, namely introverted thinking, introverted feeling, introverted sensing, and Introverted intuition in the novel I Love You as Much as I Will Let You Go by Sarah Aulia. The results of the research describe introverted personality thoughts that appear most frequently, then introverted personality feelings, introverted sensory personality, and introverted personality intuition with the following percentages: of the 50 quotes found, there are introverted personality thoughts of 48% or the equivalent of 24 data findings, introverted personality feeling as much as 34% or the equivalent of 17 data findings, introverted personality sensing as much as 12% or the equivalent of 6 data findings, and introverted personality intuition as much as 6% or the equivalent of 3 data findings. The personality of the main character in this novel is very closed. This personality has the advantage of using his mind first before speaking or doing something so he can be a good listener.